The prevalence of anxiety symptoms and disorders among ophthalmic disease patients - Zulvikar Syambani Ulhaq; Gita Vita Soraya; Nadia Artha Dewi; Lely Retno Wulandari (Therapeutic Advances in Ophthalmology, 2022)
Background: Progressive and irreversible vision loss has been shown to place a patient at risk of mental health problems such as anxiety. However, the reported prevalence of anxiety symptoms and disorders among eye disease patients vary across studies. Thus, this study aims to clarify the estimated prevalence of anxiety symptoms and disorders among ophthalmic disease patients. Methods: Relevant studies on the prevalence of anxiety symptoms and disorders among eye disease patients were collected through international databases, PubMed, Scopus, and Web of Science. A random-effects model was used to determine the pooled prevalence of anxiety symptoms and disorders among ophthalmic disease patients. Results: The 95 included studies yielded a pooled prevalence of 31.2% patients with anxiety symptoms and 19.0% with anxiety disorders among subjects with ophthalmic disease. Pediatric patients were more anxious (58.6%) than adults (29%). Anxiety symptoms were most prevalent in uveitis (53.5%), followed by dry eye disease (DED, 37.2%), retinitis pigmentosa (RP, 36.5%), diabetic retinopathy (DR, 31.3%), glaucoma (30.7%), myopia (24.7%), age-related macular degeneration (AMD, 21.6%), and cataract (21.2%) patients. Anxiety disorders were most prevalent in thyroid eye disease (TED, 28.9%), followed by glaucoma (22.2%) and DED (11.4%). When compared with healthy controls, there was a twofold increase on the prevalence of anxiety symptoms (OR = 1.912, 95% CI 1.463–2.5, p  < 0.001) and anxiety disorders (OR = 2.281, 95% CI 1.168–4.454, p  = 0.016). Conclusion: Anxiety symptoms and disorders are common problems associated with ophthalmic disease patients. Thus, comprehensive and appropriate treatments are necessary for treating anxiety symptoms and disorders among ophthalmic disease patients.